On strict ranking by pairwise comparisons - Magnot, Jean-Pierre (Annales Mathematicae Silesianae, 2026)
This paper addresses the problem of obtaining a strict ranking (i.e., a ranking without equally ranked items) of n items based on a pairwise comparisons matrix. The basic structures are described and a heuristic approach based on a condition, the R-condition is proposed. The limitations of this ranking procedure are analyzed.